Lupus in fabula. The Ovidian Metamorphosis in the Middle Ages and the Pseudo-Ovidian De lupo - Jegorow, Adam (The Motifs of Fauna and Flora in Literature and Culture, 2018)
This paper examines the role of Ovidian backdrop in the textual transmission of a medieval pseudo- Ovidian poem De lupo. The aim of the analysis is to explain in the light of medieval poetics some dynamics concerning the false authorial attribution, by showing a common understanding of thematic and functional affinities between Metamorphoses and the animal literature in the educational processes. The subsequent textual transformations are demonstrated by the manuscript evidence of three Polish 15th-century codices (Kraków, BJ 2141, 2233; Wrocław, Biblioteka Uniwersytecka, IV Q. 126), which transmit a latter alternative version of the poem.